The day the crayons quit - Daywalt, Drew.; Jeffers, Oliver (New York : Philomel Books, 2013)
When Duncan arrives at school one morning, he finds a stack of letters, one from each of his crayons, complaining about how he uses them.
Keywords: Crayons -- Juvenile fiction; Letters -- Juvenile fiction; Colors